Integration of Mindfulness and Kawruh Jiwa in Guidance and Counseling Services to Achieve Psychological Well-Being of Students in The Disruption Era - Endang Rifani (Universitas Sebelas Maret, 2019)
The purpose of this paper is to examine the guidance and counseling services by integrating mindfulness and kawruh jiwa as an effort that can be done by school counselors in shaping psychological well-being of students. The era of disruption as an era that has positive and negative impacts and provides opportunities and challenges to influence the psychological condition of students. Psychological well-being becomes important for students in establishing social relations effectively. Mindfulness and kawruh jiwa almost have the same concept that is characterized by acceptance of what it is by not judging, accepting, releasing, conscious, giving way to students to achieve psychological well-being so as to be able to develop their potential more optimally. Kawruh Jiwa as indigenous counseling is considered necessary to be applied to students so that it is not too far apart from the values and understanding of Javanese culture. Concepts and interventions are discussed in this article.